ANALYSIS THE ACTIVITIES OF ECONOMIC ENTITY ON A TIME-BASED FOR REDUCING UNNECESSARY COSTS AND IMPROVING THE PERFORMANCE OF ACTIVITIES: A FIELD STUDY - Maytham Hazim Azeez Khzaee (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
Given the current situation and the fierce competition Iraqi companies face as a result of the financial markets being invaded by a large number of competitive products offering lower prices and better quality than local products, these companies are under a lot of pressure for a variety of reasons, including the high cost of their products and the low quality of their output due to a lack of application of modern technologies, which, as one of the dairy factories in Abu Ghraib connected to the general companies for food products, aims to apply (TD-ABC) technology to identify the factory’s untapped and used energy in addition to providing more accurate and objective information in order to overcome the shortcomings of traditional costing techniques.